Comparative Analysis of the Status and Influencing Factors of Immunization Among Children Between Registered and Floating Population - Xiong, Yan; Xue, Yaqing; Jiao, Guojin; Xie, Jun; Cheng, Jingmin (Frontiers in Public Health, 2022)
Background A vaccine is an effective tool to reduce the gap between the rich and the poor and improve health equity, through which a number of serious childhood diseases can be successfully prevented or eradicated. This study is aimed to compare the current situation of vaccination and related factors among children in China's registered residents and floating population, to provide a reference for achieving the 100% vaccination rate in China. Methods The data used for this study are from the 2017 National Migrants Dynamic Monitoring Special Survey data. A self-designed questionnaire was used to collect information, such as socio-demographics, vaccination status of children, and so on, on the registered population and floating population. Descriptive statistics and a chi-square independence test were used to describe the information and to compare the vaccination status of children under different sociodemographic characteristics. Binary logistic regression was employed to analyze influencing factors associated with vaccination of children. Results The findings showed that 94.39% of children in registered residence were completely vaccinated, which was significantly higher than that of the floating children (91.68%, p < 0.001). The region, parents' education level, and marital status were found to be significant risk factors for complete vaccination of children regardless of the registered or floating population. In addition, ethnicity and length of time to the nearest medical institution were unique risk factors for complete vaccination of children in registered residence. And, health record was an independent influencing factor for vaccination of children of floating population. Conclusion Compared with registered population, floating population was at a disadvantage in using basic public health services, especially in children's vaccination. To achieve 100% vaccination for children, particular interventions should be taken for different populations.